Characterization of the life-cycle stages of the coccolithophore Emiliania huxleyi and their responses to Ocean Acidification - Rokitta, Sebastian D. (Universität Bremen, 2012)
Anthropogenic carbon dioxide emissions cause a chemical phenomenon known as Ocean Acidification (OA). The associated changes in seawater chemistry are believed to have significant impact especially on coccolithophores, unicellular calcifying primary producers that take an outstanding role in the regulation of the marine carbon pumps. This thesis investigated the calcifying diploid and the non-calcifying haploid life-cycle stages of the globally dominant coccolithophore Emiliania huxleyi, and their responses to OA. Emphasis was put on investigating the role of energy-availability (i.e., irradiance) in the manifestation of OA-responses. A suite of methods was applied to resolve the effects on the phenomenological level (growth, elemental quotas and production), the physiological level (photosynthesis, carbon acquisition) and the level of gene expression (transcriptomics). In publication I, haploid and diploid cells were compared using microarray-based transcriptome profiling to assess stage-specific gene expression. The study identified genes related to distinct cell-biological traits, such as calcification in the diplont as well as flagellae and lipid respiration in the haplont. It further revealed that the diploid stage needs to make more regulatory efforts to epigenetically administrate its double amount of DNA, and therefore strongly controls its gene expression on the basis of transcription. The haplont in turn, possessing only a single sized genome, does not require these administrative efforts and seems to drive a more unrestricted gene expression. The proteome is apparently regulated on the basis of rapid turnover, i.e., post-translational. The haploid and diploid genomes may therefore be regarded as cellular operating systems that streamline the life-cycle stages to occupy distinct ecological niches. Publication II investigated the responses of the life-cycle stages to OA under limiting and saturating light intensities. Growth rates as well as quotas and production rates of carbon (C) and nitrogen (N) ...